Analisis Pengaruh E-Learning dan Kesiapan Belajar Terhadap Minat Belajar Melalui Motivasi Belajar Sebagai Variabel Intervening Mahasiswa Program Beasiswa FLATS di Surabaya pada Masa Pandemi Covid-19 - Yemima Intan Sari; Novi Trisnawati (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
This study aims to analyze the influence of e-learning and learning readiness on learning interests through learning motivation as an intervening variable for flats scholarship students in Surabaya during the Covid-19 pandemic. The method used in this study is quantitative and the type of research is associative. The population of this study is flats scholarship students in Surabaya with a sample of 70 people. This research instrument uses questionnaires. Techniques for analyzing the data using path analysis or path analysis through the SmartPLS 3.0 program. The results of this study show that: 1) there is a significant influence between e-learning and student learning motivation; 2) there is an insignificant influence between e-learning and student learning interests; 3) there is a significant influence between learning readiness and student learning motivation; 4) there is a significant influence between learning readiness and student learning interests; 5) there is a significant influence between learning motivation and student learning interests; 6) there is an insignificant influence between e-learning and the interest in learning through student learning motivation; and 7) there is a significant influence between learning readiness and learning interests through student learning motivation.